MORTALITY RATES OF OROPHARYNGEAL CANCER WITH THEIR EPIDEMIOLOGICAL ASSESSMENT, DETERMINATION OF REGIONAL CHARACTERISTICS, TRENDS AND FORECAST FOR THE REPUBLIC OF UZBEKISTAN (World Bulletin of Public Health, 2024)
Malignant neoplasms of the head and neck represent one of the most difficult medical and social problems of modern oncology, primarily due to the large number of affected anatomical areas, the presence of complex anatomical structures included in this area. The abundant blood supply to this area causes the lightning-fast spread, rapid growth and metastasis of tumors of this localization
Keywords: Malignant neoplasms; oropharyngeal; oral; oropharynx